2020
DOI: 10.1021/acs.jpcc.9b11224
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition Routes for ε- and γ-CL-20 Crystals under High Pressures of up to 60 GPa

Abstract: The pressure-induced structural phase transitions of ε- and γ-CL-20 were studied by Raman and mid-infrared spectroscopy up to 60 GPa. In this work, the phase transition of CL-20 from the ε-phase to the γ′-phase starts at 0.9 GPa and ends at 4.4 GPa. The γ′-phase in this work is distinctly different from the γ-phase recognized by the energetic community in terms of the structure and properties. Subsequently, the η phase starts at 6.9 GPa and ends at 10.6 GPa because of the slight cage distortion. With further i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…Values for the δ1−δ6, from the optimized pressure structures, are given in the Supporting Information (Figure S1 and Table S2), from which a smooth trend is evident for all angles with the exception of δ4, which shows a pronounced change above 4.4 GPa. The absolute magnitude of the angle change does not exceed 4° however, but it may potentially account for the subtle changes observed in the previous vibrational spectroscopy study. , …”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…Values for the δ1−δ6, from the optimized pressure structures, are given in the Supporting Information (Figure S1 and Table S2), from which a smooth trend is evident for all angles with the exception of δ4, which shows a pronounced change above 4.4 GPa. The absolute magnitude of the angle change does not exceed 4° however, but it may potentially account for the subtle changes observed in the previous vibrational spectroscopy study. , …”
Section: Resultsmentioning
confidence: 71%
“…The absolute magnitude of the angle change does not exceed 4 however, but it may potentially account for the subtle changes observed in the previous vibrational spectroscopy study. 28,61 3.4 High-Pressure X-ray Powder Diffraction. In order to extend the pressure range of previous diffraction studies, 27 we conducted our 1 st compression experiment 29 at beamline I15 at the Diamond Light Source, and high quality XRPD data were obtained (using λ = 0.4847 Å) up to 7.2 GPa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] The extreme high-pressure and high-temperature conditions would lead to the changes of crystal and molecular structure, which is the focus of the study of energetic materials (EMs). In recent decades, many studies on the polymorphs [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] and decomposition [20][21][22][23][24] for CL-20 have been extensively investigated from both theoretical and experimental points of view. Using a high-pressure diamond anvil cells (DAC) with Fourier transform infrared (FTIR) spectroscopy, Russell et al identified a new high-pressure phase ζ-CL-20 at 0.7 GPa, which can undergo rapid and reversible phase transformation from γ-CL-20.…”
Section: Introductionmentioning
confidence: 99%
“…[ 13 ] Recently, Sun et al systematically studied the transformations of ε ‐ and γ ‐CL‐20 using Raman spectroscopy, mid‐IR (MIR) spectroscopy, and synchrotron XRD under quasi‐hydrostatic pressures of up to 60 GPa. [ 14 ] They explained controversial issues and proposed several new phases of CL‐20, in which the ε‐ phase to newly discovered γ′ ‐phase, η ‐phase, φ ‐phase, and ι ‐phase transitions take place near 0.9–4.4 GPa, 6.9 GPa, 28 GPa, and 50.5 GPa, respectively.…”
Section: Introductionmentioning
confidence: 99%